Use of Insulin Pump Therapy in the Pediatric Age-Group: Consensus statement from the European Society for Paediatric Endocrinology, the Lawson Wilkins Pediatric Endocrine Society, and the International Society for Pediatric and Adolescent Diabetes, endorsed by the American Diabetes Association and the European Association for the Study of Diabetes - Phillip, Moshe; Battelino, Tadej; Rodriguez, Henry; Danne, Thomas; Kaufman, Francine (Diabetes care, 2007)
To address these issues, the European Society for Pediatric Endocrinology (ESPE), the Lawson Wilkins Pediatric Endocrine Society (LWPES), and the International Society for Pediatric and Adolescent Diabetes (ISPAD) convened a panel of expert physicians for a consensus conference endorsed by the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD). The following variables should be considered in analyzing the cost benefit of CSII: acute complications, i.e., the frequency of severe hypoglycemia and DKA (including emergency department visits and hospitalizations [C: 58]); chronic complications, both micro- and macrovascular (EDIC macrovascular study [B: 95]); direct costs of supplies; indirect costs related to lost earnings of parents; and costs of other caregivers and additional care team resources.